Upaya UNICEF dalam Mengembangkan Model Gerakan Anti Perundungan terhadap Anak Sekolah melalui Program Roots di Kota Makassar Tahun 2016-2018 - Talantan, Liliani Toding; Burhan, Zulkhair (Journal of International and Local Studies, 2024)
This research aims to understand UNICEF's efforts in developing an anti-bullying movement model through the Roots Program.through the Roots Program. Bullying in school children is a familiar bullying itself has become a global phenomenon. In 2016-2018 UNICEF, together with the Government of Indonesia and the Yayasan Indonesia Mengabdi Foundation collaborated in testing the implementation of the Roots Program in Makassar City as a first phase trial. This research uses the concept of International Organizations through Clive Archer's views in understanding the role of the Roots Program in creating an anti-bullying campaign movement in schools. The results showed that there were three ways of developing the anti-bullying movement model which was implemented during the first phase of the pilot test in Makassar City, namely, 1) Roots Day anti-bullying campaign at school; 2) Formation of Agenn Perubahan; 3) Dissemination of positive messages and behaviors. This research concludes that these methods are successful in overcoming the problem of bullying in SMPN 37 and SMPN 10 Makassar.